2023
DOI: 10.1371/journal.pone.0291024
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis reveals the diagnostic and prognostic role of CDCA2 in low-grade glioma

Wenle Li,
Dong Lv,
Jieqin Yao
et al.

Abstract: Background Cell division cycle associated 2 (CDCA2), a member of the cell division cycle associated proteins (CDCA) family, is crucial in the regulation of cell mitosis and DNA repair. CDCA2 was extensively examined in our work to determine its role in a wide range of cancers. Methods CDCA2 differential expression was studied in pan-cancer and in diverse molecular and immunological subgroups in this research. Additionally, the diagnostic and prognostic significance of CDCA2 in pan-cancer was also evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…CDCA2 is involved in the cell division cycle and response to DNA damage. One study found CDCA2 expression is upregulated in ovarian tumor tissue compared with normal tissue 85 . This study also found that CDCA2 and its 100 most co-expressed genes were primarily involved in cell cycle, oocyte meiosis, progesterone-mediated oocyte maturation, p53 signaling and pyruvate metabolism pathways.…”
mentioning
confidence: 99%
“…CDCA2 is involved in the cell division cycle and response to DNA damage. One study found CDCA2 expression is upregulated in ovarian tumor tissue compared with normal tissue 85 . This study also found that CDCA2 and its 100 most co-expressed genes were primarily involved in cell cycle, oocyte meiosis, progesterone-mediated oocyte maturation, p53 signaling and pyruvate metabolism pathways.…”
mentioning
confidence: 99%